Intracellular and Extracellular Roles of Granzyme K - Bouwman, Annemieke C.; van Daalen, Kim R.; Crnko, Sandra; ten Broeke, Toine; Bovenschen, Niels (Frontiers in Immunology, 2021)
Granzymes are a family of serine proteases stored in granules inside cytotoxic cells of the immune system. Granzyme K (GrK) has been only limitedly characterized and knowledge on its molecular functions is emerging. Traditionally GrK is described as a granule-secreted, pro-apoptotic serine protease. However, accumulating evidence is redefining the functions of GrK by the discovery of novel intracellular (e.g. cytotoxicity, inhibition of viral replication) and extracellular roles (e.g. endothelial activation and modulation of a pro-inflammatory immune cytokine response). Moreover, elevated GrK levels are associated with disease, including viral and bacterial infections, airway inflammation and thermal injury. This review aims to summarize and discuss the current knowledge of i) intracellular and extracellular GrK activity, ii) cytotoxic and non-cytotoxic GrK functioning, iii) the role of GrK in disease, and iv) GrK as a potential therapeutic target.